Acquiring Reading Skill by Second Language Learners - Jayasundara, J.M.P.V.K. (Uva Wellassa University Sri Lanka, 2014)
In the field of second language (L2) learning, reading is considered as one of the significant skills needed to be developed in order to master the target language as it is being a receptive skill which leads to produce writing as well as speaking skills. Hence, considerable research now suggests that, in addition to the phonemic awareness skills which support early decoding, skilled reading also requires more general oral language competencies, particularly those involving the use of decontextualized language . The current study intends to explore how do students acquire the reading skill in the process of second language learning while investigating the ways to prevent the difficulties of reading. Accordingly, a questionnaire was employed contemplating how reading skill is acquired by the learners. Further, Uva Wellassa University has been selected as the research location, where the data were collected from 40 undergraduates, utilizing the simple random sampling method. Moreover, the statistical software, ‘Minitab 15’ has been used for analytical purposes. According to the results ascertained through the analysis, most of the respondents read through internet and newspapers representing equal percentage (43%) by each. Moreover, the motive of reading for most of them is searching latest news (30%) and having fun (22%). Furthermore, reading newspaper articles (48%) and books (35%) are graded as the best methods to acquire reading skill by the majority. Thus, the findings are beneficial in improving reading skill of L2 learners in Sri Lankan education arena assisting syllabus designers and curriculum developers providing benefits for future researches to be conducted pursuing this line of research.
Keywords: Reading; Second Language; Acquiring; Skill; English